Problems of quantifying savings within asset acquisition - Vochozka, Roman; Mares, Jaromir (Vojnotehnički glasnik / Military Technical Courier, 2019)
The article describes the application of standard methods of determining savings in the commodity acquisition, which do not impose an obligation to evaluate the centralized award system and the Methodology for the Quantification of Savings set by the Ministry for Regional Development of the Czech Republic. The process is related to the tyres within the Ministry of Defence acquired in the centralized and decentralized manners in the period 2014-2017. In the decentralized manner, higher variability of unit prices and higher variability of the number of suppliers are expected. In the centralized manner, the constant price level is predicted since the supplier is permanent during the whole period of the performance of the framework agreement for a period of two years. Statistical methods - the hypothesis testing method - are used to compare the unit prices in both manners. The comparison has been carried out by the two-sample t-test of the mean values of two selections in order to determine the differences in the amount of financial resources. It has been found that the unit prices of the centralized acquisition are higher than the unit prices of the decentralized acquisition; therefore, the centralized manner of acquisition is more expensive than the decentralized one.